Pemberdayaan Masyarakat UMKM Melalui Pembangunan Studi Kasus: Di Desa Cibatu Kecamatan Cibatu Kabupaten Garut - Naila Aulia Rahmah Virhanida; Muhammad Rafli Permanayudha; Nabila Ilmi Gumilar; Putri Aulia Tauziah (CV. Armas Suan Sejahtera, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) in rural areas plays a strategic role in promoting local economic growth and strengthening community empowerment. This study aims to examine the contribution of MSMEs to community empowerment and to identify local potentials that can be optimized to enhance business sustainability in Cibatu Village, Garut Regency. The research adopts a qualitative descriptive approach, with data collected through field observations, in-depth interviews, and documentation. The findings indicate that MSMEs in Cibatu Village have grown by utilizing local natural resources and cultural heritage as the foundation for developing distinctive products, including traditional handicrafts and local food processing. The presence of MSMEs has contributed to increased household income, job creation, and the strengthening of local socio-economic capacity. However, several challenges remain, such as limited access to capital, low levels of digital literacy, and weak marketing networks. These constraints hinder MSMEs from expanding their market reach and improving competitiveness. Therefore, collaborative support from village governments, educational institutions, and the private sector is essential, particularly in the form of entrepreneurship training, business management assistance, and the adoption of digital technologies for marketing and distribution. The study concludes that strengthening MSMEs based on local potential can serve as a key driver of sustainable rural economic development, provided it is supported by structured, participatory, and continuous empowerment strategies.